ANTITUSSIVE MEDICINAL HERBS - AN UPDATE REVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The cough is a protective reflex mechanism that removes foreign material and secretions from the bronchi and bronchioles of the airways; it is inappropriately stimulated in various situations like inflammation of the respiratory tract or neoplasia. In these cases, cough has a pathological character and it is necessary sometimes to use cough-suppressant drugs. The most frequently used antitussive drugs in clinical conditions produce adverse effects like depression of the respiratory centre, decreased secretion in the bronchioles and inhibition of ciliary activity, increased sputum viscosity, decreased expectoration, hypotension and constipation acts as limitation to the therapy. Use of herbal drugs is increasing all over the world for various ailments including antitussive activity as they are safe and devoid of adverse effects. Medicinal plants are an important source for the discovery of novel bioactive compounds, which have served and continue to serve as lead molecules for the development of new drugs. Thus this review may provide an insight into herbs possessing antitussive activity.